EVALUASI POPULASI MIKROBA FUNGSIONAL PADA PUPUK ORGANIK KOMPOS (POK) MURNI DAN PUPUK ORGANIK GRANUL (POG) YANG DIPERKAYA DENGAN PUPUK HAYATI - Sahwan, Firman Laili; Wahyono, Sri; Suryanto, Feddy (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Organic fertilizer is a fertilizer that is expected to improve the physical, chemical, andÃ‚Â biological properties of the agricultural land resources, which is undergoing fertilityand productivity degradation. Compost is one of the organic fertilizers produced fromÃ‚Â the biological decomposition process by a consortium of microorganisms, includingfunctional microorganisms. To make it easier for farmers and efficiency in the use ofÃ‚Â organic fertilizer, organic fertilizer will be further processed into granular form and is calledÃ‚Â Granules Organic Fertilizer (POG). In the manufacturing process, namely at the time ofÃ‚Â drying using a rotary dryer, was suspected of using high temperatures to kill microbesÃ‚Â (including functional microbial) that naturally exist in the organic compost fertilizer (POK),Ã‚Â which is the raw material for POG. To increase the presence of functional microbialÃ‚Â populations, the POG which has produced before, then added with bio fertilizer that isÃ‚Â rich in microbial functional. This research was conducted to determine and evaluate theÃ‚Â total microbial population and functional microbial in pure POK, compared with the totalÃ‚Â microbial population and functional microbial in the POG are enriched with bio-fertilizer.Ã‚Â The results showed: There is an indication to the higher number of total microbialÃ‚Â population in the POK, who showed by total fungi population, compared with the POG.Ã‚Â The number of functional microbial population, as shown by bacterial phosphate solventÃ‚Â and non-symbiotic bacteria that are fastening N in POK, very high and already meetsÃ‚Â the criteria to be called as a biological fertilizer. The amount is not significantly differentÃ‚Â compared to the POG that is already enriched with bio fertilizer that is rich in microbialÃ‚Â functional. There is an indication of the influence of high heating using a rotary dryer,Ã‚Â in the POG manufacturing process against the decreasing of the amount of microbialpopulation that are resulting in the POG, including functional microbial